Failure Analysis of Bend Tube Preheater on Heat Recovery Steam Generator - R. Sony Endardo Putro; Arif Hariyadi; Suwarno Suwarno (JMES: The International Journal of Mechanical Engineering and Sciences, 2017)
The combined cycle power plant (PLTGU) is the second largest percentage of electrical production method which is 26% of all electrical production technology in Indonesia. One of the components in combined cycle power plant is the heat-recovery steam generator (HRSG), which serves as heat-exchanger between hot gasses from gas turbine cycle and water from steam turbine cycle. There are four stages on HRSG, preheater, economizer, evaporator, and superheater. In the present work, there is a case of thinning on a bend tube preheater which exceeds the tolerance limits, therefore the purposes of this research determine the cause of failure and determine the failure mechanism on bend tube preheater. Thinning of bend tube preheater occurred due to corrosion from both the inside surface and outside surface. Corrosion that occurred on the inside surface of bend tube preheater caused by a reaction between water and metal surface of the tube. Corrosion on the outside surface could be happen caused by a reaction between the hot gas and metal surface of the tube. Largest thinning rate occurred on bend area of bend tube preheater caused by deformation itself, it induces local reduction of breakdown potential.